Isolation of escherichia coli 0157:h7 in animal originated foods in kars region - Özkan Aslantaş; Pınar Yıldız (Eurasian Journal of Veterinary Sciences)
In this study, the presence o) Escherichia coli 0157:H7 in a total ol 460 animal originated foods consisting of 200 ground beet and meat products, 260 raw milk and milk products sold in Kars region were investigated. In addition to 460 animal originated food samples, 60 cattle carcass samples taken from Kars Municipality Slaughteftiause were investigated to delect contamination of carcasses with Escherichia coli 0167:H7, Although Escherichia coli 0157.H7 was not isolated from food samples, Escherichia coli 0157:H- serotype were isolated from 2 of 100 raw milk, 1 of ground beef, 1 of white cheese. But, Escherichia coli 0157 was not isolated from cattle carcass samples. As a result, the presence of Escherichia coli 0157:H7 in different kind of animal originated foods has shown that This agent could be important for public health as a vehicle ol transmission to man